Attempts to evaluate locus suicide recombination and its potential role in B cell negative selection in the mouse - Denis-Lagache, Nicolas; Oblet, Christelle; Marchiol, Tiffany; Baylet, Audrey; Têteau, Ophélie; Dalloul, Iman; Dalloul, Zeinab; Zawil, Lina; Dézé, Ophélie; Cook-Moreau, Jeanne; Saintamand, Alexis; Boutouil, Hend; et al. (Frontiers in Immunology, 2023)
Introduction In mature B cells, activation-induced deaminase reshapes Ig genes through somatic hypermutation and class switch recombination of the Ig heavy chain (IgH) locus under control of its 3’ cis-regulatory region (3’RR). The 3’RR is itself transcribed and can undergo “locus suicide recombination” (LSR), then deleting the constant gene cluster and terminating IgH expression. The relative contribution of LSR to B cell negative selection remains to be determined. Methods Here, we set up a knock-in mouse reporter model for LSR events with the aim to get clearer insights into the circumstances triggering LSR. In order to explore the consequences of LSR defects, we reciprocally explored the presence of autoantibodies in various mutant mouse lines in which LSR was perturbed by the lack of Sµ or of the 3’RR. Results Evaluation of LSR events in a dedicated reporter mouse model showed their occurrence in various conditions of B cell activation, notably in antigen-experienced B cells Studies of mice with LSR defects evidenced increased amounts of self-reactive antibodies. Discussion While the activation pathways associated with LSR are diverse, in vivo as well as in vitro, this study suggests that LSR may contribute to the elimination of self-reactive B cells.